Determinan Keterlibatan Perempuan dalam Gerakan Radikalisme - Rindha Widyaningsih; Kuntarto Kuntarto (Assosiation of Islamic Education Lecturer of Universitas Jenderal Soedirman, 2020)
This article aims to provide an overview of women motivational factors involved in radicalism movements. Understanding the determinants of women's involvement in the radicalism movement is an effort to explain the increasing number of women's involvement in radicalism. The involvement of women in the radicalism movement is not new, but it seems strange because behind this, women are no longer just supporters behind the scenes, but directly in real action. The method used in this article is descriptive qualitative by conducting a literature review on the phenomenon of women's involvement in the radicalism movement. The results of the study show that the profile of radical actors has transcended the gender barrier. There are no specific categories for being targeted by radical groups. The determinants of women's involvement in the radicalism movement are caused by religious factors, group pressure, political factors, and personal reasons.